Effect of Polyaniline Polymers with Boric Acid and Multi-Walled Carbon Nanotube on Dye Sensitive Solar Cells Performance - Tas, R. (Polish Acad Sciences Inst Physics, 2021)
In this study, polyaniline: boric acid/carbon nanotube (PANI-BA)/MWCNT conductive polymers were chemically synthesized by the oxidative polymerization method using H5IO6 (periodic acid) as the initiator. PANI-BA conductive polymers were synthesized for a 1:1 H-5 IO (6)/aniline molar ratio. During the synthesis, 5%, 10%, and 15% MWCNT were added to the medium at various weight percentages, respectively. Results were compared with MWCNT-doped and undoped polymer. Structural properties of the conducting polymers were characterized by the XRD, SEM, and DC conductivity measurements. For the first time, their applications as a counter electrode (CE) in dye-sensitized solar cells (DSSCs) were examined. The photovoltaic performance of DSSCs was evaluated by the current density-voltage (J-V) and external quantum efficiency measurements. The obtained photovoltaic results indicate that the ideal additive ratio is 10% MWCNT when compared with pure PB. Then, the current density increases from 3.47 mA/cm(2) to 4.91 mA/cm(2) with this additive rate as well as the power conversion efficiency of the batteries. It was determined that the efficiency reaches the maximal value of 1.15% from 0.69%. These results showed that the doping of ideal MWCNT ratio in DSSCs is an effective way to increase the conversion efficiency of DSSCs.
Keywords: Dsscs; Pani; Boric Acid; Mwcnt; Solar Cells Efficiency